Development and Cross-Validation of a Predictive Equation for Fat-Free Mass in Brazilian Adolescents by Bioelectrical Impedance - Costa, Roberto Fernandes da; Silva, Analiza M.; Masset, Kalina Veruska da Silva Bezerra; Cesário, Tatianny de Macêdo; Cabral, Breno Guilherme de Araújo Tinoco; Ferrari, Gerson; Dantas, Paulo Moreira Silva (Frontiers in Nutrition, 2022)
Bioelectrical impedance analysis (BIA) is one of the most used techniques for assessing body composition in a clinical setting and field approaches, as it has the advantages of being easy to apply, fast and non-invasive, in addition to its relatively low cost. However, the available predictive equations need to be valid for the evaluated subjects. This study aimed to verify the validity of several published BIA equations in estimating fat-free mass (FFM) among Brazilian adolescents, in addition to develop and cross-validate a BIA equation to estimate FFM appropriate for Brazilian adolescents. This is a cross-sectional study with 257 adolescents (128 girls) aged 10 to 19 years, randomly divided into two groups: development (n = 172) and cross-validation (n = 85). The standard technique for assessing FFM was DXA. Paired t-test, multiple regression, and Bland–Altman plots were used to test the validity of the proposed models, as well as to perform cross-validation of the model. The equation derived in this study was: FFM = – 6.456 + 0.577 (Height2/Resistance) + 0.237 Weight + 0.080 Reactance – 2.063 Sex + 0.097 Height + 0.224 Age; r2= 0.92; SEE= 2.49 kg; the new equation for FFM showed better agreement when compared to the equations developed in other countries. In conclusion, the newly developed equations provide a valid FFM estimation and are recommended for Brazilian adolescents with similar characteristics.